Arif Hidayah’s Authorship in the “Memories of Home” - Saputra, Sandi Jaya (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2023)
Authorship is an attitude of a creative worker, which in this context is a photojournalist that can develop over time. In this study, researchers examine the form of ideas that exist in Arif Hidayah in visualizing the Tamansari community with the title “Memories of Home”. This study aims to determine the form of Arif Hidayah’s authorship in terms of aesthetic competence, personal implications and the meaning of Arif Hidayah himself in understanding substance. The researcher used qualitative research methods with an authorship case study approach. Data collection was carried out through in-depth interviews, observation and literature studies. The results showed that, (1) Arif Hidayah chose the type of composition, lighting and display in accordance with Arif Hidayah’s personal ideas, (2) Arif Hidayah’s personality has implications for creating the subject’s background within the scope of education, work, family and interests that is in Arif Hidayah to visualize the Tamansari community as a victim of eviction, (3) All meanings in visualizing the Tamansari community, Arif Hidayah always keeps the meaning in terms of the understanding that exists in Arif Hidayah, (4) The idea in Arif Hidayah’s photo project is the connection between his background ideas and Arif Hidayah’s mastery of the technical aspects of photography itself. These aspects are interconnected because Arif Hidayah’s imagination regarding the Tamansari community is based on memories and memories of his past, which are unconsciously conveyed through journalistic photography techniques in the “Memories of Home” project.